البناء الدرامي في شعر بلند الحيدري - يوسف, جابر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يسعى هذا البحث إلى الوقوف على أهم مكونات البنية الدرامية في تجربة بلند الحيدري الشعرية، نظراً لما تمثله الدراما من حضور لافت في مستويات هذه التجربة بسبب امتلاكها مقومات الحركة والتفاعل . وقد رأينا أن رصد تلك المكونات في نصوص الشاعر يسهم في التعرف على تجربة شعرية غنية في حركة شعرنا الحديث من جهة، ويسهم في كشف خصوصية هذه التجربة بالدخول إليها، ورصد أبرز مكونات البنية الدرامية فيها بوصفها الأكثر حضوراً وغنى وفاعلية من جهة أخرى. This research aims to shed light on the most important constituents of dramatic structures in Al-Haidari's poetic experience. The significant presence of dramatization in this experience is due to its being full with action and reaction. Pointing out these constituents in Al-Haidari's poetry contributes to making available such a rich poetic experience through manifesting its dramatic constituents which are the richest and most prominent on the other hand.